GREEN ACCOUNTING : PEMAHAMAN DAN KEPEDULIAN DALAM PENERAPAN (STUDI KASUS PADA PABRIK KECAP LELE DI KABUPATEN PATI) - Yuliana, Yunu Kurnelia; Sulistyawati, Ardiani Ika (Solusi, 2021)
This research was conducted at Lele Soy-sauce Factory located in Pati District, Central Java. This reaserch aims to find out if green accounting is already applied in the Lele Soy-sauce Factory and is already doing green cost for the recording of green accounting that has be done. This reaserch uses qualitative descriptive methods, with the probles of case studies. Researches use observation techniques, interviews, as well as documentation on research objects. In addition, researchers also choose the informant according to what the researchers would ask and with the informant that really understands about the Lele Soy-sauce Factory. The informant interviewed there are 3, namely : leaders, cooks, and also waste-processing employees from Lele Soy-Sauce Factory. From the research result can be known that in the Lele Soy-sauce Factory has done green accounting for factory waste to be released into rivers and trenches in a factory. But it has not done green cost for the issurance of green accounting funds that have been implemented.  Keywords : green accounting, green cost, UMKM Kecap.